Chitosan coated - porous low expansion vermiculite for efficient removal of cesium from radioactive wastewater - Bo Zhang (KeAi Communications Co., Ltd., 2021)
Radioactive elements have very important applications in practical life and work. The long-lived 137Cs has a half-life of 30.2 years, it is easily absorbed by the human body. At present, the treatment methods of 137Cs are mainly adsorption, ion exchange, co-precipitation and membrane separation technology. Among them, the adsorption method is widely used because of its low cost and easy availability, and with the continuous upgrading and improvement of the removal methods, the removal cost is also rising, so it is important to develop inexpensive and high removal rate adsorbent materials. Based on this, porous adsorbents made of pre‑sodiumed low expansion vermiculite modified by urea porogenesis and polyglutamic acid covalent grafting followed by chitosan coating had been used to remove Cs+. The proposed adsorbent was successfully applied for radioactive Cs removal to be used as the potential candidate in Fukushima nuclear wastewater treatment. It showed that the porous expanded vermiculite modified with low swelling, with urea as porogen and polyglutamic acid added to increase the negative charge vacancies on the expanded vermiculite surface, could greatly improve the chemisorption capacity of Cs+ after chitosan coating. The maximum removal rate for radioactive 137Cs+ was 97.91%, and 89.89% of 137Cs+ could be effectively removed in 0.5 h. Even in the presence of competing ions such as K+, the adsorbent material still has a good adsorption effect. The maximum desorption rate of 98.43% was achieved after elution by CaCl2.